Energy dependence of a radiophotoluminescent glass dosimeter for HDR 192Ir brachytherapy source. Issue 2 (26th December 2018) - Hashimoto, Shimpei; Nakajima, Yujiro; Kadoya, Noriyuki; Abe, Kota; Karasawa, Katsuyuki
Abstract : Purpose: We determined correction factors for absorbed dose energy dependence and intrinsic energy dependence for measurements of absorbed dose to water around an 192 Ir source using a radiophotoluminescent glass dosimeter (RPLD) calibrated with a 4‐MV photon beam. Methods: The ratio of the absorbed dose to the water and the average absorbed dose to RPLD for the 192 Ir beam relative to the same ratio in a 4 MV photon beam defines the absorbed dose energy dependence and was determined at distances of 2–10 cm (at intervals of 1 cm) from the 192 Ir source in a water phantom using the egs_chamber user code. The RPLD was calibrated to measure absorbed dose to water, D w, in a 4 MV photon beam using an ionization chamber, which was also used to measure absorbed dose to water, D w, in a water phantom using the 192 Ir source. The detector response radiophotoluminescence (RPL signal per average absorbed dose in the detector) in the 192 Ir beam relative to that in the 4 MV photon beam (the relative intrinsic efficiency) was determined experimentally. Finally, the beam quality correction factor was obtained as the quotient between the absorbed dose energy dependence and the relative intrinsic efficiency and corrects for the difference between the beam quality Q 0 used at calibration and the beam quality Q used in the measurements. Results: The relative dose ratio of the average absorbed dose to water relative to RPLD ranged from 0.930 to 0.746, and the beam quality correction factor ranged from 0.999 to 0.794 for distances of 2–10 cm from the 192 Ir source. The relative detector response to an 192 Ir source and a 4‐MV photon beam was 0.930, and it did not vary significantly with distance. Conclusions: These results demonstrate that corrections for absorbed dose energy dependence and intrinsic energy dependence are required when using an RPLD to measure with sources different from the reference source providing the primary calibration.